Openness, Specialization, and the External Vulnerability of Developing Countries - Barrot, Luis-Diego; Calderon, Cesar; Serven, Luis (World Bank, Washington, DC, 2016)
Deepening real and financial integration of developing countries into the world economy has prompted renewed interest in the contribution of external shocks to their macroeconomic fluctuations. This paper revisits the issue using four decades of annual data for a large sample of developing countries. The paper implements a conditionally-homogeneous panel vector autoregression with exogenous variables to model GDP fluctuations in these countries. It uses sign restrictions to identify four external structural shocks -– demand, supply, monetary, and commodity shocks -– and analyzes how their impact on growth is shaped by countries' policy and structural framework. External shocks are found to account for a small share of the forecast error variance of GDP, especially at short horizons. However, their contribution has been on the rise in recent decades. Further, global monetary shocks have become the leading external source of GDP volatility in developing countries. The paper presents a quantitative assessment of the effects of real and financial opening up, as well as those of commodity specialization, on the impact of external shocks on GDP. The results suggest that increasing openness can account for the increasing trend in the volatility attributable to external shocks, as well as the changing roles of different shocks. Moreover, commodity-intensive developing countries are found to be more vulnerable than the rest to all types of external shocks, not just commodity shocks.